Cover Picture: Low‐Temperature Preferential Oxidation of Carbon Monoxide on Pt3Ni Alloy Nanoparticle Catalyst with Engineered Surface (ChemCatChem 1/2016). Issue 1 (January 2016) - Hwang, Sang Youp; Yurchekfrodl, Eric; Zhang, Changlin; Peng, Zhenmeng
Abstract : The cover shows preferential oxidation of carbon monoxide (PROX) on surface of octahedral Pt3 Ni alloy nanoparticle. The image is inspired by reflection and refraction of a prism, in which reflected H2 stream representing no reaction and refracted CO2 stream representing selective CO oxidation. In their Communication, S. Y. Hwang et al. report improved PROX property by engineering surface of the Pt3 Ni alloy nanoparticle catalyst. Comparing to pure Pt and spherical Pt3 Ni, the octahedral Pt3 Ni exhibits both outstanding activity and 100% selectivity in a broadened operation temperature window. More information can be found in the Communication by Hwang et al. onpage 97 in Issue 1, 2016 (DOI:10.1002/cctc.201500783 ).